Pembuatan 3D Motion Graphic Objek Wisata TANJUNGRIAU FISHERISM Menggunakan Aspek Spatial, Temporal, Live Action, dan Typography - Ahmad Saropi; Riwinoto Riwinoto; Syania Husna Mutiara (Politeknik Negeri Batam, 2019)
Motion graphic is used in entertain and advertising industry, it effectively works to inform a product or service as visuals communication media. In this research, a motion graphic was developed to socialize a tourism campaign that will be named as Tanjungriau Fisherism Batam. A multimedia development method was used to make this motion graphic, known as Villamil Molina method. This method has five phases of its development step. The first phase is development, its contain concept and story idea making. The second phase is reproduction, its contain Skenario and storyboard making. Then, the production phase working on the 3D modeling process, animation, dubbing, rendering, final editing using video editor and continued with the postproduction phase which contains alpha test and beta test. The last phase is delivery, to publish the motion graphic to society. The result of this research shows respondent agreement percentage with spatial 91.55%, temporal 89%, live action 90,44% and typography 84% which means the motion graphic was effective to inform Tanjungriau Fisherism as tourism campaign.